Przemiany w położeniu kobiet w Niemczech Zachodnich po II wojnie światowej – kontynuacje i przełomy - Jedynakiewicz-Mróz, Katarzyna (Przegląd Nauk Historycznych, 2014)
The article presents the main changes of the situation of women in Western Germany after the Second World War. The cosiderations are based on the femal diaries from this period, as well as on the specialist literature.The first part of the text shows professional and educational activity of women in Germany in the years 1945–1949 and the femal part in the restoring of the country from the war damages. The second part of the article presents the occurence of the return to the traditional patterns of feminity in Federal Republic of Germany in time of the Christian Democracy rules (1949–1965). The third part of the cosiderations shows the effects of „the 1968 Revolution” for the women’s situation in Western Germany in time of the domination of the Social Democrats in this country (1969–1982). The fourth part of the text presents the increase of the real position of women in Federal Republic of Germany in the Eighties, in the context of the development of the civil society in West Germany.